INFLUENCE OF BRAND IMAGE AND THE QUALITY OF SERVICE TO THE DECISION TO STAY AT REDDORZ PONDOK LABU - Muhammad Zaqi; Gagih Pradini (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study was conducted on purpose to help examining and analyzing the Brand Image and Quality of Service affect the Decision to Stay at Reddorz Pondok Labu. To find out and analyze the quality of brand image and service like what is dominant to influence the decision to stay at Reddorz Pondok Labu. The study was conducted at Reddorz Pondok Labu. The results indicated that brand image and also service quality gives such a positive and also significant influence toward the decision to stay at Reddorz Pondok Labu. This means that the decision to stay is determined by the brand image and quality of service of a hotel or guesthouse that provides comfort to every consumer. Sampling technique used is purposive sampling techniques. The data were collected using the souce of primary data by givig set of questionnaires to 99 respondents. The analysis applied is testing techniques that exist in SPSS 23. The study results proved that the variables of Brand Image and Service Quality, together produce data that affect the Decision to Stay at Reddorz Pondok Labu.